Genomic analysis of Acinetobacter baumannii DUEMBL6 reveals diesel bioremediation potential and biosafety concerns - Nizam Uddin; Monjima Islam Prova; Muttasim Billaha; Tasnimul Arabi Anik; Rahat Uzzaman; Nadia Haider; Faruk Islam; Humaira Akhter; Anowara Begum (PLoS ONE, 2026)
This study investigates the bioremediation potential of bacterial isolates from diesel-contaminated soils in Dhaka, Bangladesh. A total of 34 morphologically distinct bacterial strains were isolated from hydrocarbon-polluted sites, with Acinetobacter baumannii emerging as the dominant species (41.2%), followed by Pseudomonas otitidis and Klebsiella pneumoniae (11.8% each). Genetic screening revealed that 32.35% of isolates harbored the alkB gene (alkane hydroxylase), while 58.82% carried catE (catechol-2,3-dioxygenase), indicating a strong predisposition for aromatic hydrocarbon degradation. Following turbidimetric screening of 34 bacterial isolates, 11 demonstrating superior growth were selected for gravimetric degradation assessment. Among these, isolate MB 1002 ( Pseudomonas nitroreducens ) demonstrated the highest degradative capability at 46.92%, followed by MB 751 ( Acinetobacter baumannii ) at 41.18% and MB 750 ( Pseudomonas aeruginosa ) at 39.16%. The MB 1002 and MB 751 both were positive for alkB. FTIR analysis revealed that both MB 751 and MB 1002 contribute to diesel degradation, with MB 751 showing stronger oxidation patterns due to the presence of carboxyl functional groups. Due to its superior oxidative capability, MB 751 (designated A. baumannii DUEMBL6) was selected for whole-genome sequencing. The sequence analysis of A. baumannii DUEMBL6 (deposited as JBLODW000000000) revealed: (1) hydrocarbon degradation genes ( alkB , ssuD , catechol dioxygenases); (2) 7 biosynthetic gene clusters including siderophores (100% similarity to baumannoferrin); and (3) complete xenobiotic degradation pathways for aliphatic/aromatic compounds. Despite its bioremediation potential, A. baumannii DUEMBL6 harbored 26 antibiotic resistance genes (e.g., blaOXA-338 , adeABC efflux pumps) and 33 virulence factors (e.g., csu pilus, biofilm genes), with an 86.1% pathogenicity probability. These findings highlight A. baumannii DUEMBL6’s dual role as a promising bioremediation agent and a potential public health risk, necessitating careful strain selection for environmental applications.